Virus Latency and the Impact on Plants - Takahashi, Hideki; Fukuhara, Toshiyuki; Kitazawa, Haruki; Kormelink, Richard (Frontiers in Microbiology, 2019)
Plant viruses are thought to be essentially harmful to the lives of their cultivated crop hosts. In most cases studied, the interaction between viruses and cultivated crop plants negatively affects host morphology and physiology, thereby resulting in disease. Native wild/non-cultivated plants are often latently infected with viruses without any clear symptoms. Although seemingly unharmful, these viruses pose a threat to cultivated crops because they can be transmitted by vectors and cause disease. Reports are accumulating on infections with latent plant viruses that do not cause disease but rather seem to be beneficial to the lives of wild host plants. In a few cases, viral latency involves the integration of full-length genome copies into the host genome which, in response to environmental stress or during certain developmental stages of host plants, can become activated to generate and replicate episomal copies, a transition from latency to reactivation and causation of disease development. The interaction between viruses and host plants also may lead to integration of partial-length segments of viral DNA genomes or copy DNA of viral RNA genome sequences into the host genome. Transcripts derived from such integrated viral elements (EVEs) may be beneficial to host plants, for example, by conferring levels of virus resistance and/or causing persistence/latency of viral infections. Studies on viral latency in wild host plants might help us to understand and elucidate the underlying mechanisms of latency and provide insights into the raison d'être for viruses in the lives of plants.